Alteración de la discriminación auditiva y déficit de la atención de estudiantes de nivel primario entre 6-8 años en colegios de trujillo - Sánchez Chu, Enrique (2015)
A prospective cohort study was conducted to determine whether the altered auditory discrimination is associated with attention deficit 494 younger students was assessed between the ages of 6 and 8 years of state schools and individuals in Trujillo, who test was applied in identifying symptoms of people with attention deficit twice a week for six months, the sample was distributed 247 patients with attention deficit for group A and 247 without attention deficit for group B, who will I apply Wepman test to assess Auditory discrimination. We found there was a significant association between attention deficit disorder and auditory discrimination. It was found that the frequency of Altered Auditory Discrimination in relation to attention deficit was 43.7%. It was reported that the prevalence of impaired auditory discrimination was 25.3% and female predominance, also found that the intervener’s diseases of the ear against alterations of discrimination were allergic rhinitis, impacted cerumen, alterations of the tympanic membrane and serous otitis media. In conclusion, impaired auditory discrimination is associated with attention deficit in children of primary level between 6-8 years of colleges of Trujillo